2004
DOI: 10.1007/s00066-004-1183-8
|View full text |Cite
|
Sign up to set email alerts
|

On the Actual State of Industrial Quality Assurance Procedures with Regard to 106Ru Ophthalmic Plaques

Abstract: Legislation has to make sure that the use of radioactive material on humans be, among other things, permitted as a matter of principle only, if the dose rate calibration can be traced to standards of a federal authority of measurement procedures. Furthermore, special leakage tests for radiation sources which come into direct contact with body fluids should be established. A historical retrospect reveals that the greatest changes have taken place in the indication of the dose rates of (125)I sources. Since the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 13 publications
0
10
0
1
Order By: Relevance
“…6). However, the difference in the relative dose compared to the findings of Kaulich et al 24 is up to 3.5%. The measurements conducted by the manufacturer prior to 2001 show a relative dose that is up to 6% lower than the PENELOPE calculations and up to 9% lower than the measurements conducted using small-volume scintillators.…”
Section: F Cgd Applicatormentioning
confidence: 78%
See 1 more Smart Citation
“…6). However, the difference in the relative dose compared to the findings of Kaulich et al 24 is up to 3.5%. The measurements conducted by the manufacturer prior to 2001 show a relative dose that is up to 6% lower than the PENELOPE calculations and up to 9% lower than the measurements conducted using small-volume scintillators.…”
Section: F Cgd Applicatormentioning
confidence: 78%
“…The only available reference containing dose data for the CGD applicator is the work of Kaulich et al, 24 who analyzed the quality assurance procedures followed by the manufacturer in producing the applicators. One criticism of the mea applicator measured with the manufacturer's improved measurement system.…”
Section: F Cgd Applicatormentioning
confidence: 99%
“…This seems tolerable considering the fact that the dose rate of the currently used ruthenium applicators can only be measured to an accuracy of ± 25% (95% CI) [6].…”
Section: Discussionmentioning
confidence: 99%
“…In the case of more focal tumor growth the use of beta emitting eye applicators may be an alternative. However, grave therapyrelevant shortcomings of the industrial quality assurance of ophthalmic plaques as shown by Kaulich et al [10] have to be taken into consideration. Another alternative treatment of more superficial focal tumor manifestations could be the use of soft X-ray irradiation units as shown by Willner et al [31] for the treatment of recurrent pterygia.…”
Section: Discussionmentioning
confidence: 99%